2021
DOI: 10.1039/d1sm01186c
|View full text |Cite
|
Sign up to set email alerts
|

Scaling laws to predict humidity-induced swelling and stiffness in hydrogels

Abstract: From pasta to biological tissues to contact lenses, gel and gel-like materials inherently soften as they swell with water. In dry, low-relative-humidity environments, these materials stiffen as they de-swell with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…S3) in accordance with previous testing procedures. 27 Indeed, the stiffness of the hydrogels increases as crosslinker ratio increases (Fig. 2b, blue).…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…S3) in accordance with previous testing procedures. 27 Indeed, the stiffness of the hydrogels increases as crosslinker ratio increases (Fig. 2b, blue).…”
mentioning
confidence: 91%
“…We and others have shown that changing crosslinking simply changes ϕ poly (or the equilibrium swelling state) and minimally affects other molecular properties. 27,50 That is, in eqn (2), the monomer size, a , and excluded volume, v , do not change with crosslinker amount—only ϕ poly changes. As such, hydrogels that differ only by crosslinking can be viewed as being a part of the same polymer family.…”
mentioning
confidence: 99%
See 3 more Smart Citations